Identifikasi kebiasaan pemanasan pada mata pelajaran pendidikan jasmani di sekolah - Andi, Imam; Samodra, Yohanes Tauvan Juni; Gustian, Uray (UIR Press Bekerjasama dengan International Association of Physical Education and Sports, 2021)
Warming up is the beginning to core training, if the warm-up is fun, the core exercises will be fun and vice versa if the warm-up is not fun for students, the core exercises will also not be fun. The purpose of the study was to explore information on warming that occurred in physical education subjects. The research method used is survey research with a quantitative approach. The research instrument used a questionnaire given to students with a total of 83 people, namely 52 junior high school students and 31 elementary school students. The results showed that the average score of 82.3% of junior high school students and 93% of elementary school students answered yes. Based on the results of the study, it showed that warming up was done the old way, namely jogging and of course it was boring to do.